Sistema multi-híbridos na cultura do milho: viabilidade técnica e econômica em zonas de manejos - Baron, Felipe Arthur (2019)
Brazil is consolidated as the third largest maize producer in the world and the second largest exporter, with a high domestic consumption of cereal, as it is one of the world's leading producers of animal protein. The use of productivity zones, defining different homogeneous environments within an agricultural area is an important tool for the treatment of spatial variability. Thus, the increase in plant population per area may be an interesting factor in the search for high yields. However the response of the best plant population is dependent on the hybrid in question. Thus there is an ideal plant population for each production system when seeking high yields. The objective of this work is to identify the best adjustment of plant population and corn hybrids for two yield zones (high and low). Experiments with three maize hybrids were conducted in Boa Vista das Missões - RS, in an agricultural production area, with central pivot irrigation system, in the 2015/2016 agricultural year. Productivity zones were delineated from overlapping productivity maps. In each yield zone, three maize hybrids were tested: (a) Agroeste 1677 VT PRO3®, (b) BioGene 7318 YH and (c) Pioneer 1630 H. In each hybrid, five plant populations were tested: (i) 60,000, (ii) 75,000, (iii) 90,000, (iv) 105,000 and (v) 120,000 plants ha-1. The experiments were conducted in a randomized block design and arranged in a tri-factorial scheme (2x3x5), with four replications. Sowing was performed on August 30, 2015, using a spacing of 0.50 m between rows. Six components of yield and grain yield were evaluated. Through the equations obtained for productivity, the maximum technical efficiency and maximum economic efficiency were determined. The parameters evaluated were submitted to the normality test and subsequently to the analysis of variance (ANOVA) (p≤0.05). Significance was verified by the F test, the means of the qualitative factors (Productivity Zone and Hybrid) were compared by the Tukey test (p <0.05), while plant population were compared by regression analysis (p < 0.05). There is an average increase in yield of 5.35% with the use of a multi-hybrid sowing system. Even working with a single hybrid per field justifies the use of varied seed rate, however, it is necessary to know in detail the hybrid that will be used. There are differences between the optimum plant population for each yield zone, and the range of variation is extremely dependent on the hybrid being worked, requiring a timely adjustment for each genotype.